KAJIAN TEKNIS PENGGUNAAN METODE FULL OUTFITTING BLOCK SYSTEM (FOBS) PADA PRODUKSI PEMBANGUNAN KAPAL BOX SHAPE BLOCK CARRIER (BSBC) M 229/230 KAPASITAS 50.000 DWT DI PT. PAL INDONESIA - Jatmiko, Sukanto; Chrismianto, Deddy (Department of Naval Architecture - Diponegoro University, 2008)
PT. PAL Indonesia used Full Outfitting Block System (FOBS) methods to abridge ship construction time. But, production accomplishment still frequent to late, so, implementation of those methods at PT. PAL Indonesia in the production of Box Shape Bulk Carrier (BSBC) M 229/230 ship construction or known as STAR 50 need to investigated. The data interpretations were done by doing observation, gather planning data, and monthly production report of Box Shape Bulk Carrier ship between Februarys 2007- April 2008 periods. Then, calculating percentage of FOBS implementation at PT. PAL Indonesia with constrains factor from the data’s. The conclusions based on the analysis and discussions from this research are percentage of FOBS implementation method at PT. PAL Indonesia is 71,633 %, constrain factors of FOBS implementation method at PT. PAL Indonesia are material overdue (6,122%), human resources (4,246%), design (3,954%), production facility (2.820%), and experience (1,244%)